Anxiety about the speed of technological development: Effects on job insecurity, time estimation, and automation level preference - (:unkn) unknown (Elsevier Ltd, 2021)
Technology is developing rapidly. Every year, new products and services are produced that may affect the way employees work in organizations. Following and adapting to technological developments may be an individual challenge. People may experience anxiety in this process. Also, automation technologies may lead to a perception that individuals may lose their jobs soon. This may affect employees' choices in the possible human-robot collaboration process. In this study, we reached out to employees from various sectors via internet survey. The statistical analyses showed that concerns about the speed of technology affects employees' job insecurity caused by robots and the perception of job insecurity related to their work affects the level of automation they prefer in robots. New studies on this subject may contribute to the efficiency of human-robot cooperation which is expected to happen soon. Also, it may contribute to highlighting the anxiety experienced by employees during the development of technology. © 2021 Elsevier Inc.
Keywords: Automation levels; Employee anxiety; Job insecurity; Technological development; Technological unemployment